Unlocking dandelion (Taraxacum mongolicum)’s hidden treasure: enzyme-hydrolyzed polysaccharides with enhanced bioactivity for ROS defense and developmental protection - Yue Zheng; Juan Du; Yuan Wang; Wenwen Wang; Xiaoping An; Jingwei Qi (Chemical and Biological Technologies in Agriculture)
Abstract Dandelion (Taraxacum mongolicum) is widely used as a natural additive in food, pharmaceutical, and cosmetic industries. In this study, we applied pectinase-mediated enzymatic hydrolysis to dandelion to enhance its bioactivity. The results showcased that enzyme treatment disrupted the cell‐wall matrix, turning the raw material from yellowish-green to dark brown and releasing bound polysaccharides. The hydrolyzed extract polysaccharide (EDP) exhibited higher polysaccharide content (180.72 mg/g), an improved water extraction rate (33.22%), and a reduced molecular weight. In vitro assays revealed superior antioxidant performance in EDP—84.06% DPPH and 59% hydroxyl-radical scavenging—along with stronger reducing power. Furthermore, in an AAPH-induced zebrafish model, EDP more effectively supported heart rate and normal development while notably reducing reactive oxygen species (ROS) accumulation, lipid peroxidation, and cell death. Collectively, these findings highlight the potential of enzymatic hydrolysis as a strategy to boost the bioactive properties of dandelion, offering valuable insights for its use in functional foods and natural antioxidants. Graphical abstract